HUBUNGAN KUNJUNGAN PRABEDAH TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT DUSTIRA CIMAHI - Arief Kurniawan; Budi Santoso; Nur Pudyastuti Pratiwi (Jurnal Cakrawala Ilmiah, 2024)
Preoperative visits have become part of clinical practice in many hospitals. Preoperative visits aim to provide information to patients about the surgical and anesthesia procedures that will be performed. This study aims to explore the relationship between preoperative visits and patient satisfaction to improve the quality of health services. This research method uses an observational descriptive approach through questionnaires to elective surgery patients at Dustira Hospital Cimahi. There were 543 patients undergoing surgery under anesthesia during April 2024, while 215 patients met the inclusion criteria and completed the questionnaire. Based on the sample characteristics, the majority of patients were women (54.9%), followed by the age group of 31-45 years (44.2%), undergoing major surgery (63.3%), and general anesthesia (57.2%). Patient satisfaction levels, when correlated with sample characteristics, showed that highly satisfied patients were male, aged 46-60 years, underwent minor surgery, and received general anesthesia, while other groups were at satisfactory levels. Patient satisfaction based on the questionnaire showed that most patients were satisfied with the service, with the highest order being satisfied (55.8%), followed by highly satisfied (37.4%), neutral (13.5%), and dissatisfied (8.1%). Patients felt satisfied and highly satisfied with anesthesia and surgical services, while no patients felt dissatisfied. This condition indicates that preoperative visits can increase patient satisfaction